Prediksi Jumlah Kunjungan Wisatawan Mancanegara ke Indonesia - Aida Meimela (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Predict the number of foreign tourist's visit Indonesia. In 2020 the Ministry of Tourism and Creative Economy has targeted the number of foreign tourists visiting Indonesia as many as 17 million visits. However, the number of foreign tourist visits decreased cumulatively (January- July 2020) by 64.64 per cent compared to the same period in 2019. Based on these conditions, it is significant to make accurate predictions to see if the target will be achieved or not in the future. One of the prediction methods used is Seasonal ARIMA (Autoregressive Integrated Moving Average). This model predicted the predictable number of foreign tourists visit in 2020 forecast to pass the target